Effect of operating parameters on the minimum fluidisation velocity of an inclined fluidised bed - Taib, Mohd. Rozainee (Penerbit UTM Press, 2003)
Fluidisation phenomena in an inclined fluidised bed (IFB) systems are poorly understood and receive less attention as compared to that of vertical fluidised bed although in practice there are many fluidised bed systems not vertically oriented. The objective of this work is to investigate the effect of inclination angle, particle size and particle composition to the minimum fluidisation velocity (Umf). The experiments were conducted in a rectangular IFB of dimension, 7 Ã— 50 cm fitted with a 2 mm thick metal distributor plate with 1 mm holes diameter (2.98 % opening area), water manometer, flow meter and compressor for fluidising air supply. The gradual decreasing velocity method was used to investigate the Umf. Three operating parameters were observed, namely angle of inclination, particle diameters and the compositions of mixed particles. The experimental results showed that the Umf of the particles is lower at higher angle of inclinations. The smaller particles have a lower Umf. The mixed sand with higher smaller particles mass fraction also has a lower Umf. Therefore, the effects of inclination angle and smaller particles mass fractions in the mixed sand to the Umf were observed to follow an inverse function, while, the particle size is linearly related to the Umf.